2022
DOI: 10.1101/2022.01.04.474746
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

hPSC-Derived Enteric Ganglioids Model Human ENS Development and Function

Abstract: The enteric nervous system (ENS) plays a central role in gut physiology and mediating the crosstalk between the gastrointestinal (GI) tract and other organs. The human ENS has remained elusive, highlighting the need for an in vitro modeling and mapping blueprint. Here we map out the developmental and functional features of the human ENS, by establishing robust and scalable 2D ENS cultures and 3D enteric ganglioids from human pluripotent stem cells (hPSCs). These models recapitulate the remarkable neuronal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 63 publications
(87 reference statements)
0
16
0
Order By: Relevance
“…Next, we set out to determine if our hPSC-derived enteric neurons (henceforth referred to as “stage 1 2D enteric neurons” based on their differentiation stage and format) contain the same neuronal diversity as other published enteric neuron datasets. We compared the neurochemical composition of our dataset to hPSC-derived stage 1 and stage 2 ganglioid (3D) enteric neurons published by our group 21 , primary fetal human enteric neurons published by Teichmann and colleagues 40 , as well as primary adult human colonic enteric neurons published by Regev and colleagues 20 . For neurotransmitters, we utilized a two-step neurochemical identity-defining approach, that our group has reported previously, to identify all the cells that belong to six neurotransmitter identities: serotonergic, GABAergic, catecholaminergic, glutamatergic, cholinergic, and nitrergic 21 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Next, we set out to determine if our hPSC-derived enteric neurons (henceforth referred to as “stage 1 2D enteric neurons” based on their differentiation stage and format) contain the same neuronal diversity as other published enteric neuron datasets. We compared the neurochemical composition of our dataset to hPSC-derived stage 1 and stage 2 ganglioid (3D) enteric neurons published by our group 21 , primary fetal human enteric neurons published by Teichmann and colleagues 40 , as well as primary adult human colonic enteric neurons published by Regev and colleagues 20 . For neurotransmitters, we utilized a two-step neurochemical identity-defining approach, that our group has reported previously, to identify all the cells that belong to six neurotransmitter identities: serotonergic, GABAergic, catecholaminergic, glutamatergic, cholinergic, and nitrergic 21 .…”
Section: Resultsmentioning
confidence: 99%
“…We compared the neurochemical composition of our dataset to hPSC-derived stage 1 and stage 2 ganglioid (3D) enteric neurons published by our group 21 , primary fetal human enteric neurons published by Teichmann and colleagues 40 , as well as primary adult human colonic enteric neurons published by Regev and colleagues 20 . For neurotransmitters, we utilized a two-step neurochemical identity-defining approach, that our group has reported previously, to identify all the cells that belong to six neurotransmitter identities: serotonergic, GABAergic, catecholaminergic, glutamatergic, cholinergic, and nitrergic 21 . We found that all six neurochemical identities are represented in our cultures, recapitulating the neurotransmitter diversity of other datasets (Figure S4F).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations